2016
DOI: 10.19082/2855
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative Color Doppler Sonography of Lower Extremity Veins on Postoperative Outcomes in Candidates of Saphenectomy: A Randomized Clinical Trial

Abstract: BackgroundDoppler sonography is a type of sonography used for imaging the blood flow in the vessels and heart. This technique uses ultrasound waves with high frequency. In some patient candidates for venous graft, the identification of the suitable vein is not possible with clinical examination.ObjectiveThis study compared the effects of preoperative color Doppler sonography of lower extremity veins on the postoperative outcomes of saphenectomy.MethodsThis randomized clinical trial was conducted on 100 candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…The possible risk of bias was assessed using either the Cochrane Risk of Bias Assessment [18] or the ROB-INS-I tool [19] for the RCTs [20,21] and non-RCTs [6,12,22], as appropriate (Table 1). Both risk of bias assessment tools include several domains whereby in which regard each study is evaluated independently.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible risk of bias was assessed using either the Cochrane Risk of Bias Assessment [18] or the ROB-INS-I tool [19] for the RCTs [20,21] and non-RCTs [6,12,22], as appropriate (Table 1). Both risk of bias assessment tools include several domains whereby in which regard each study is evaluated independently.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Of 4514 papers screened in this systematic review, 36 papers underwent full-text assessment with final inclusion of five studies [6,12,[20][21][22] (Fig. 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it has been reported that deep venous thrombosis (DVT) has a growing incidence. 1 The clinical manifestations of the acute phase include: the affected limb is swollen and painful, with changed skin color and high skin temperature (lower temperature when the artery is affected), feeling heavy, mild fever, and limited activity 2 ; some severe cases may also appear blue leg, increased muscle tonus of lower limb, with a possibility of occurring osteofascial compartment syndrome. At the same time, the swollen muscle compresses the artery of lower extremity, leading to pulselessness and distal limb ischemia, which would lead to whiteleg, or even worse, limb necrosis and amputation.…”
Section: Introductionmentioning
confidence: 99%